Legal Accountability in AI-Driven Banking Crimes: Regulatory Gaps and the Roles of Developers, Owners, and Users in Indonesia - Cynthia Putri Guswandi (Nomos : Jurnal Penelitian Ilmu Hukum, 2025)
The development of Artificial Intelligence (AI) in the banking sector has triggered various potential criminal acts, presenting new challenges in the field of criminal law. Existing regulations reveal that the current legal framework has yet to adequately accommodate the complexity of cases involving AI systems, particularly with regard to assigning legal responsibility to developers, owners, and users. Most regulations remain focused on conventional criminal acts. This raises questions about the adequacy of Law No. 27 of 2022 on Personal Data Protection, various regulations issued by the Financial Services Authority (OJK), and the Indonesian Banking Artificial Intelligence Governance Guidelines in providing comprehensive legal protection. This study employs normative legal research with a comparative approach to regulatory systems in Singapore and China. It focuses on analyzing legal gaps and challenges in applying the principle of criminal liability to actors involved in AI-based banking systems. The findings highlight the necessity of strengthening regulations and updating legal doctrines to anticipate the complex risks posed by AI, while fostering accountability that adapts to technological advancements.